2001
DOI: 10.1183/09031936.01.00086201
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological treatment of the biochemical defect in cystic fibrosis airways

Abstract: The understanding of the biochemical defect in cystic fibrosis (CF) has advanced considerably since discovery of the CF gene in 1989 and characterization of its product. Studies showing that the abnormality in chloride flux could be corrected by transfection of wild-type cystic fibrosis transmembrane conductance regulator (CFTR) complimentary deoxyribonucleic acid (cDNA) have led to gene therapy trials on both sides of the Atlantic. However, gene therapy as a treatment for CF has yet to be realized.Pharmacolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
4

Year Published

2002
2002
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 63 publications
0
8
0
4
Order By: Relevance
“…4 Defective protein trafficking is thought to result from improper protein folding and/or incorrect molecule assembly and is associated with a growing number of human diseases. 5,6 With the recognition that some trafficking-defective membrane proteins are functional when induced to insert into the plasma membrane, the correction of protein trafficking abnormalities has been a therapeutic goal in a number of diseases, such as cystic fibrosis 7 and nephrogenic diabetes insipidus. 8 In LQT2, we previously reported that the HERG N470D mutation is trafficking defective when studied at a physiological temperature.…”
mentioning
confidence: 99%
“…4 Defective protein trafficking is thought to result from improper protein folding and/or incorrect molecule assembly and is associated with a growing number of human diseases. 5,6 With the recognition that some trafficking-defective membrane proteins are functional when induced to insert into the plasma membrane, the correction of protein trafficking abnormalities has been a therapeutic goal in a number of diseases, such as cystic fibrosis 7 and nephrogenic diabetes insipidus. 8 In LQT2, we previously reported that the HERG N470D mutation is trafficking defective when studied at a physiological temperature.…”
mentioning
confidence: 99%
“…Na via de fosforilação por PKA, essa proteína é ativada pelo aumento da concentração de AMPc via ciclase de adenilil (AC). Uma vez fosforilada, CFTR torna-se ativa e possibilita o efluxo de Cl -através da membrana apical da célula (20) .…”
Section: O Gene Da Fibrose Cística E Cftrunclassified
“…Como a proteína CFTR sofre a influência de diversos fatores para seu funcionamento normal que afetam a sua migração RE -Golgi -membrana plasmática -endossomo, sua expressão gênica e a sua ativação por fosforilação, existem diversos possíveis alvos moleculares para testar novas drogas no controle da ausência de efluxo de Cl -em pacientes com FC e CFTR -ΔF508 (20) . Dentre estes fatores estão: reguladores da migração citoplasmática, ativadores da expressão gênica, moduladores da fosforilação e inibidores de "stop codons".…”
Section: 381tratamento Farmacológico Para Cftrunclassified
See 2 more Smart Citations